FROM THE WORLD RELIGION VIEW TO THE GEERTZIAN APPROACH IN INTERPRETING A CULTURE: An Excursion to Traditional Economic Ritual of Javanese in Langsih Cave - Taufiqurrohim, Taufiqurrohim (AL-TAHRIR, 2019)
Abstract: Langsih cave offers the space for the ritual which fulfills the requirement of Javanese tradition called Pesugihan defining as a supernatural practice and belief in getting rich quick through mysticism and the people should do such a ritual in a sacred place with the particular rule. Through the symbol and ritual experiences, there would find how the people chronologically believe in the sacred ritual that would conducive to the wealth of the ritual. Thus, this paper firstly tries to point out the role of Langsih cave as the site of traditional economic ritual for Javanese culture. The next discussion is examining the existence of pesugihan as on how the worldview representation to the ritual. The last is arguing the optional perspective based on Geertzian approach, which it offers interpretative theory of the culture at the semiotic experience due to its explication â€œconstruing social expressions on their surface enigmaticalâ€ but it still needs an explanation. The paper shows that the traditional economic ritual is surely a practice transcending from the ancestor unconsciously and the culture seems to be blurred because the role of the tough should be more rational, modernized or religious.Ø§Ù„Ù…Ù„Ø®Øµ: ÙŠØ³ÙˆØ±ØºØ§Ø±Langsih Â Ø§Ù„ÙØ±Ø§Øº Ù„Ø·Ù‚ÙˆØ³ Ø§Ù„Ø°ÙŠ ÙŠØ£Ø¯ÙŠ Ø¥Ù„ÙŠ Ø´Ø±ÙˆØ· ØªÙ‚Ù„ÙŠØ¯ Ø§Ù„Ø¬Ø§ÙˆÙŠØ© Ø§Ù„ØªÙŠ ØªØ³Ù…ÙŠpesugihan Â . Ø§Ù„Ù…Ù‚ØµØ¯ Ù…Ù† Â pesugihan ÙŠØ¹Ù†ÙŠ Ù…Ù…Ø§Ø±Ø³Ø© Ø§Ù„Ø®Ø§Ø±Ù‚ Ùˆ Ø§Ù„ØªØµØ¯ÙŠÙ‚ Ù„ØªÙƒÙˆÙ† ØºÙ†ÙŠØ§ Ø¨Ø³Ø±Ø¹Ø© Ø¨ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØµÙˆÙ, ÙˆÙˆØ¬Ø¨ Ù„ÙƒÙ„ Ù†ÙØ± Ø§Ù„Ø·Ø§Ø¹Ø© Ø¹Ù„ÙŠ Ø§Ù„Ø·Ù‚ÙˆØ³ ÙÙŠ Ø£ÙŠ Ù…ÙƒØ§Ù† Ùˆ Ø¨Ù‚ÙˆØ§Ø¹Ø¯ Ù…Ø¹ÙŠÙ†. Ø¨ØªÙÙ‡ÙŠÙ… Ø§Ù„Ø±Ù…Ø² ÙˆØªØ¬Ø±Ø¨Ø© Ø§Ù„Ø·Ù‚ÙˆØ³ Ø³ÙŠÙƒÙˆÙ† Ù‡Ù†Ø§Ùƒ Ø·Ø±ÙŠÙ‚Ø© Ù„Ù„Ù†Ø§Ø³ Ù„ÙÙ‡Ù… Ø¨Ø´ÙƒÙ„ Ø·Ø¨ÙŠØ¹ÙŠ Ø¹Ù† Ø§Ù„Ø·Ù‚ÙˆØ³ Ø§Ù„Ù…Ù‚Ø¯Ø³Ø© Ø§Ù„ØªÙŠ ØªÙØ¶ÙŠ Ø¥Ù„Ù‰ Ø§Ù„Ø«Ø±ÙˆØ© Ø§Ù„Ø·Ù‚ÙˆØ³ÙŠØ©. ÙÙÙŠ Ø£ÙˆÙ„ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø³ØªØ¸Ù‡Ø± Ø¥Ù„ÙŠ Ø¯ÙˆØ± ØºØ§Ø±Langsih Â Â ÙƒÙ…ÙƒØ§Ù† Ø§Ù„Ø·Ù‚ÙˆØ³ Ø§Ù„Ø¥Ù‚ØªØµØ§Ø¯ Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠ Ù„Ø«Ù‚Ø§ÙØ© Ø§Ù„Ø¬Ø§ÙˆÙŠØ©. ÙˆÙ…Ù†Ø§Ù‚Ø´Ø© Ø¨Ø¹Ø¯Ù‡Ø§ ÙŠØ¹Ù†ÙŠ Ø§Ù„Ø¨ØØ« Ø¹Ù† Ø§Ù„ØªÙ…Ø«ÙŠÙ„ Ø§Ù„Ù†Ø¸Ø±Ø© Ø§Ù„Ø¹Ø§Ù„Ù…ÙŠØ© Ø¹Ù„ÙŠ ØªÙ„Ùƒ Ø§Ù„Ø´Ø¹ÙŠØ±Ø©. ÙˆØ§Ù„Ø£Ø®Ø± ÙŠØ¹Ù†ÙŠ Ø§Ù„ØªÙ†Ø§Ø²Ø¹ Ø¹Ù† Ù…Ù†Ø¸ÙˆØ± Ø§Ù„Ø¥Ø®ØªÙŠØ§Ø±ÙŠ Ø¨Ù†Ø§Ø¡ Ø¹Ù„ÙŠ Ù†Ù‡Ø¬Geertzian Â , Ø§Ù„Ø°ÙŠ ÙŠØ¹Ø±Ø¶ Ø¹Ù† Ø§Ù„Ù†Ø¸Ø±ÙŠØ© Ø§Ù„ØªÙØ³ÙŠØ±ÙŠØ© Ø¨ØªØ¬Ø±Ø¨Ø© Ø´Ø¨Ù‡ Ù„Ø£Ù† ØªÙØ³ÙŠØ± "ØØ¯ Ø§Ù„ØªØ¹Ø¨ÙŠØ± Ø§Ù„Ø¥Ø¬ØªÙ…Ø§Ø¹ÙŠ ÙÙŠ Ø³Ø·ØÙ‡Ù… Ø¨ØºØ§Ù…Ø¶" ÙŠØØªØ§Ø¬ Ø£Ù„ÙŠ Ø§Ù„ØªØ´Ø±ÙŠØ. ØªÙˆØ¶Ø Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ±Ù‚Ø© Ø£Ù† Ø§Ù„Ø·Ù‚ÙˆØ³ Ø§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠØ© Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠØ© Ù‡ÙŠ Ø§Ù„Ù…Ù…Ø§Ø±Ø³Ø§Øª Ø§Ù„ÙÙ„Ø³ÙØ© Ø§Ù„Ù…ØªØ¹Ø§Ù„ÙŠØ© Ù…Ù† Ø£Ø³Ù„Ø§Ù Ø¯ÙˆÙ† ÙˆØ¹ÙŠ Ùˆ ÙƒÙ…Ø§ Ù„Ùˆ ÙƒØ§Ù†Øª Ø§Ù„Ø«Ù‚Ø§ÙØ© Ù…Ø®ÙÙŠØ© Ù„Ø£Ù† Ø§Ù„Ø¯ÙˆØ± Ø§Ù„Ø°ÙŠ ÙŠØ¬Ø¨ Ø§Ù„Ù‚ÙŠØ§Ù… Ø¨Ù‡ Ù‡Ùˆ ØªØµØ¨Ø Ø£ÙƒØ«Ø± Ø¹Ù‚Ù„Ø§Ù†ÙŠØ© Ø£Ùˆ ØØ¯ÙŠØ«Ø© Ø£Ùˆ Ø¯ÙŠÙ†ÙŠØ©.Â Â Â Â  Â Â Â Â Â Â Â Â Â Abstrak: Gua Langsih menawarkan ruang untuk ritual yang memenuhi persyaratan tradisi Jawa yang disebut pesugihan yang didefinisikan sebagai praktik supranatural dan kepercayaan untuk menjadi kaya dengan cepat melalui mistisisme dan orang-orang harus mamatuhi ritual di suatu tempat dengan aturan tertentu. Melalui interpretasi simbol dan pengalaman ritual, akan ada cara yang orang secara alami percaya pada ritual sakral yang akan kondusif bagi kekayaan ritual. Maka, makalah ini pertama-tama mencoba menunjukkan peran gua Langsih sebagai tempat ritual ekonomi tradisional untuk budaya Jawa. Diskusi selanjutnya adalah penelusuran keberadaan representasi pandangan dunia terhadap ritual tersebut. Yang terakhir adalah memperdebatkan perspektif opsional berdasarkan pendekatan Geertzian, yang menawarkan teori interpretatif semi-pengalaman karena penjelasan "membatasi ekspresi sosial di permukaan mereka secara misterius" tetapi masih perlu penjelasan. Makalah ini menunjukkan bahwa ritual ekonomi tradisional tentu saja merupakan praktik transendentalisme dari leluhur secara tidak sadar dan budaya tersebut seolah ditutup-tutupi karena peran yang harus dibuat adalah menjadi lebih rasional, modern ataupun agamis.